Corporate social responsibility in agribusiness in the context of human rights protection in Eastern Europe - D. Kovach; O. Kovach (Law. Human. Environment, 2025)
The purpose of this study was to analyse corporate social responsibility (CSR) in Eastern European agribusiness through the lens of human rights protection, particularly environmental and labour rights. The research methodology was based on an interdisciplinary approach, including the analysis of regulations, the study of international CSR standards, and an empirical analysis of the activities of agribusinesses in Ukraine, Romania, and the Czech Republic. The findings revealed that CSR implementation considerably contributes to the enjoyment of environmental rights, specifically the right to a clean environment. This is achieved through the rational use of natural resources, introduction of renewable technologies, and reduction of pollutant emissions. In the labour sphere, CSR protects the rights of employees by creating decent working conditions, preventing discrimination, and providing social guarantees such as health insurance and professional development. The analysis of large agricultural holdings, such as MHP (Ukraine), Trans-Oil (Romania), and Agrofert (Czech Republic), showed that companies actively integrate CSR into their business strategies, particularly in the area of employee rights protection, specifically through the creation of safe working conditions, social guarantees, and professional skills development. Therewith, the study revealed major barriers to systematic implementation of CSR in the context of human rights protection. The primary obstacles include insufficient state control over compliance with environmental and labour standards, as well as limited engagement of civil society in monitoring the activities of agribusinesses. This complicates systemic change and increases the risk of human rights violations. The conclusions highlighted the need to strengthen state control, develop incentive mechanisms for business, including tax benefits, and actively engage civil society in monitoring. The findings confirmed the value of integrating CSR into business strategies to ensure sustainable development and human rights protection